Review of the Principles of Justice in Fixed-Time Work Agreements and Their Implications for Law and Development in the Era of the Job Creation Law - Safrida, Safrida (International Journal of Educational Research & Social Sciences, 2024)
This study aims to examine the application of the principle of justice in fixed-term employment agreements (PKWT) in Indonesia within the context of the Job Creation Law. The principle of justice serves as a fundamental guideline in employment relationships, particularly in ensuring a balance between the rights and obligations of workers and employers. This research employs a normative legal approach, which involves a literature review and analysis of legal regulations, doctrines, and principles of justice relevant to PKWT. The findings indicate that the application of the principle of justice in PKWT during the era of the Job Creation Law still faces various challenges, particularly regarding the protection of workers' rights and equality in employment relationships. This study also discusses the legal implications of implementing PKWT on economic development and labor reform in Indonesia. Specifically, the impact of PKWT has the potential to accelerate economic growth through flexibility in the labor market, but it may also create uncertainty for workers, affecting social stability. Therefore, strategies are needed to ensure that labor reforms not only support economic growth but also uphold justice and protection for all parties involved.